IMPROVING STUDENT MATHEMATICS LEARNING ACHIEVEMENT THROUGH GROUP INVESTIGATION LEARNING MODELS - Nartini Nartini; Darmadi Darmadi (Social Sciences, Humanities and Education Journal (SHE Journal), 2020)
Although famous as a favorite junior high school, mathematics is still a scourge for most students of SMPN 1 Madiun. As a result, students' mathematics learning achievement does not meet the KKM. The group investigation learning model is one alternative to improve student learning achievement. Classroom action research with the stages of planning, implementing, observing, and reflecting on each cycle is used to improve this situation. Planning is carried out according to the results of the identification and reflection of the previous cycle. Implementation according to plan. Observations are emphasized on the implementation of learning, increasing learning achievement, and student responses. Reflections are made to make the necessary improvements so that learning objectives are achieved. The results showed that students have positive attitudes and responses to mathematics learning with the group investigation model on the subject of Social Arithmetic. Mathematics learning achievement of students of class VII B of SMP Negeri 1 in 2018/2019 in the subject of Social Arithmetic by using a group investigation model increased with an average value of 81.5 so that it was categorized quite well. Teachers can use the group investigation model as an alternative to improving students' mathematics learning achievement.